Zkušenosti s přípravou 68Ga-PSMA-11 - Budinský, Michal; Vyšinský, Petr; Řehák, Zdeněk; Adam, Jan (Chemické listy, 2022)
The radiopharmaceutical 68Ga-PSMA-11 represents aradiopharmaceutical drug without marketing authoriza-tion for the prostate cancer diagnosis in a specific treat-ment program. In respect of the radiopharmaceutical tech-nology, the difficultness of the preparation of 68Ga-PSMA-11 is comparable to that of conventional radiopharmaceuti-cals.
Keywords: prostatický specifický antigen; Radiopharmaceuticals; Česká republika; glutamátkarboxypeptidasa II; radiofarmaka; Prostate-Specific Antigen; Humans; Research Design; lidé; mužské pohlaví; Radioisotopes; Male; radionuklidy; Czech Republic; výzkumný projekt; Glutamate Carboxypeptidase II